ASSET RETRENCHMENT DAN PERFORMA PERUSAHAAN: EFEK PADA BERBAGAI STAGE LIFE CYCLE PERUSAHAAN - Yudiyanto Yudiyanto; Yanti Manggarani (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
Asset retrenchment strategy is one way for a company to stay afloat in financial distress and to improve firm performance. However, previous research has mostly focused on companies operating in mature industries. This study aims to examine the effect of Assets Retrenchment on firm performance in different competitive environments. The population used in this study are companies from non-financial sector listed on the Indonesia Stock Exchange between 2010 and 2020. The sample size was determined using the purposive sampling method. Research data was collected from Osiris then analyzed using regression analysis techniques using SPSS software. Overall, asset retrenchment strategy is positively correlated with increasing firm performance. The implications of the findings will be taken into account in decision-making for management in choosing a turnaround strategy in dealing with financial distress and to improve company performance.